Development of Science Student Worksheet with STEAM Approach with Local Papuan Flora Content at Al-Jihad Elementary School, Sorong City: Pengembangan Lembar Kerja Siswa IPA dengan Pendekatan STEAM Bermuatan Flora Lokal Papua di SD Al-Jihad Kota Sorong - Anggraini, Nisa Juniar; Agnesa, Oki Sandra; Ramli, Muhammad (JENIUS :Journal of Education Policy and Elementary Education Issues, 2025)
This study focuses on the low availability of integrated teaching materials with the STEAM approach and Papuan local wisdom content in science learning. The purpose of the study was to produce a product in the form of a student worksheet with a STEAM approach, containing local Papuan flora in science learning, to determine the feasibility of a student worksheet with a STEAM approach containing local Papuan flora, and to determine the responses of teachers and students to the student worksheet. The researcher used the 4D model research and development (R&D) method with four stages, including 1) define, 2) design, 3) develop, and 4) disseminate. The validation results by material experts showed that the student worksheet, with a STEAM approach containing local Papuan flora, got an average score of 89% in the category (Very Valid). The validation results by media experts showed an average score of 92% in the category (Very Valid). The results of the field practitioner trial showed a value of 92%, which was included in the category (Very Practical). In comparison, the results of the group and field tests reached 88% in the category (Very Practical). Thus, the developed student worksheet has proven valid and practical for science learning. It is hoped that developing this student worksheet can strengthen students' understanding of science material and increase interest in learning through connections with the surrounding environment.